SKILL ACQUISITION THEORY AND THE ROLE OF RULE AND EXAMPLE LEARNING (Journal of Contemporary Philology, 2021)
The present paper presents an overview of research in support of Skill Acquisition Theory (SAT) in relation to learning a second language. Skill acquisition is defined as a gradual transition from conscious and effortful use of a cognitive skill to more automatic and fluent use of the same. As such, SAT provides a particularly insightful avenue for understanding second language development in the context of instructed second language learning. The paper focuses on the right conditions for the transition of declarative representations of second language grammar rules into procedural ones, claiming that it is only when learners have a real need for grammar rules that they become beneficial for the learner. The timing of providing grammar rules as well as the role of cognitive variables such as language learning aptitude and working memory are also addressed. Finally, future directions for explicit learning and sample second language classroom activities regarding grammar instruction are suggested.
Keywords: skill acquisition theory; declarative knowledge; procedural knowledge; explicit learning; individual differences